The Amman suicide bombings: On the strategy of Abu Musab al-Zarqawi - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2005)
On November 9 simultaneous suicide bombings in three luxury hotels shook the Jordanian capital Amman. The perpetrators were Iraqis who traveled in from the neighboring country and acted on the instructions of the Jordanian terrorist Abu Musab al Zarqawi. Before he became active in Iraq, Zarqawi had, since the early 1990s, fought exclusively against the Hashemite monarchy, so these recent attacks could be read as the logical continuation of this direction line of struggle. However, they must be seen in a new, more comprehensive strategic context: since 2004 Zarqawi is trying to drive the US and its allies out of Iraq, in order to erect an Islamic state there. Following on from that, the 'holy war' (jihad) is to be taken to the neighboring countries of Syria, Jordan, Saudi Arabia and Kuwait. The ultimate goal is the 'liberation' of Jerusalem. Since the summer of 2005 the Zarqawi group has been increasingly pursuing these goals in parallel, in Iraq and its neighboring states. (SWP-Comments / SWP)
Keywords: 320